Rotational propensities in the state selection of NH3+ by pulsed-field ionization - Dickinson, H; Rolland, D; Softley, T (1997)
NH+ 3 ions have been prepared in unique vibration-rotation states ν+ 2, N+, K+, by pulsed-field ionization of high Rydberg states of NH3, populated by two-colour multiphoton excitation. The selected states, ranging from ν+ 2 = 0 to 7 and N+, K+ ≤ 4 are accessed via the B and C′ states as intermediates. The application of multichannel quantum defect theory to the understanding of the rotational propensities in the mass-analysed threshold ionization spectra is discussed. It is demonstrated that the interactions of the Rydberg pseudo-continuum both with bound Rydberg states and with other continua can be modelled.